CONTEMPORARY ENERGY SECURITY STUDIES: THEORETICAL ASPECTS - K. V. Trachuk (MGIMO University Press, 2013)
The article represents an attempt to analyze the contemporary theoretical framework of energy security research as part of international relations and foreign policy studies. Neorealism and neoliberalism are the key theoretical schools having the strongest impact on energy security research. Authors inspired by the neorealist approach, including J. Russell, D. Moran and M.Clare, insist on the role of individual state actors that seek to maximize their energy supply or their position as an energy exporter. The key areas of study of the neorealist school include military aspects of energy security and resource nationalism. The neoliberal framework, represented by such scholars as A. Goldthau and J.M.Witte, focuses on the role of institutions, international cooperation and liberal markets. Unlike neorealists, neoliberals believe that global energy markets provide the necessary conditions for the peaceful cooperation of all players. Constructivist approaches represent an interesting alternative to the “neo-neo” debate, but still remain marginal. Although proponents of neorealist and neoliberal frameworks disagree on several key points, a large number of scholars, both in Russia and abroad, prefer a combined approach based on elements on neorealist and neoliberal theories. The combined analytical framework is used by such leading Western researchers as D.Yergin, J. Stanislaw, A.Korin and G.Luft, as well as many Russian scholars, including N.Mironov, S.Zhiznin and Y.Borovsky.